Structure and optical properties of a new AgBiW2O8 polymorph. (15th September 2019) - Sotelo, Paola; Moore, Michael; Galante, Miguel T.; Longo, Claudia; Rajeshwar, Krishnan; Suescun, Leopoldo; Macaluso, Robin T.
Graphical abstract: A novel polymorph of β-AgBiW2 O8 was prepared for the first time by a simple arc melting method. β-AgBiW2 O8 belongs to the scheelite structure type and can be described with Ag/Bi bisdisphenoids and WO4 tetrahedra. The main peak in diffuse reflectance spectroscopy measurements reveal absorption of blue light. Abstract: In this work, we report a novel polymorph of AgBiW2 O8, which was synthesized by a simple arc melting method. The structural details of this compound were determined by X-ray powder diffraction, and elemental composition was confirmed with ICP-AES. β-AgBiW2 O8 adopts the scheelite structure type with tetragonal space group I 41 /a and lattice parameters a  =  b  = 5.3019(3) and c  = 11.678(2) Å. Structural details and optical properties are discussed in detail. Diffuse reflectance spectroscopy (DRS) measurements of β-AgBiW2 O8 showed light absorption profile extended to the visible region, which suggests the material has a smaller band gap energy than Bi2 WO6, as expected due to contribution of Ag d-orbitals to the electronic structure.